2014
DOI: 10.1371/journal.pone.0101394
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Analysis for the Assessment of Phylogenetic Diversity and Biogeography in Hyphomonas Bacteria from Diverse Marine Environments

Abstract: Hyphomonas, a genus of budding, prosthecate bacteria, are primarily found in the marine environment. Seven type strains, and 35 strains from our collections of Hyphomonas, isolated from the Pacific Ocean, Atlantic Ocean, Arctic Ocean, South China Sea and the Baltic Sea, were investigated in this study using multilocus sequence analysis (MLSA). The phylogenetic structure of these bacteria was evaluated using the 16S rRNA gene, and five housekeeping genes (leuA, clpA, pyrH, gatA and rpoD) as well as their concat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…It was later found that ATCC 43869 T did not conform to the description of the type strain of Hyphomonas rosenbergii. The resequenced 16S rRNA gene sequence of ATCC 43869 T (under GenBank accession number KF880383) shows only 92.84 % similarity to the original 16S rRNA gene sequence (Li et al, 2014). The 16S rRNA gene sequence of DSM 17769 T was identical with our result (KF880383) (http:// www.dsmz.de/catalogues/details/culture/DSM-17769.html).…”
supporting
confidence: 71%
“…It was later found that ATCC 43869 T did not conform to the description of the type strain of Hyphomonas rosenbergii. The resequenced 16S rRNA gene sequence of ATCC 43869 T (under GenBank accession number KF880383) shows only 92.84 % similarity to the original 16S rRNA gene sequence (Li et al, 2014). The 16S rRNA gene sequence of DSM 17769 T was identical with our result (KF880383) (http:// www.dsmz.de/catalogues/details/culture/DSM-17769.html).…”
supporting
confidence: 71%
“…, Li et al. , Glaeser and Kämpfer ). The 16S rRNA gene due to its conservation is useful for generic placement in cyanobacteria (Boyer et al.…”
Section: Discussionmentioning
confidence: 97%
“…Sporichthyaceae are ubiquitous in freshwaters (Newton et al, 2011), and were abundant in oligosaline arctic lakes (Theroux et al, 2012) as well as in the Baltic Sea (Andersson et al, 2010;Piwosz et al, 2013), and so it is likely that more bacteria of this family tolerate salinity of up to 3-4 PSU, and, to a lesser extent 7-8 PSU. Similarly, typically marine members of the Hyphomonas genus (Li et al, 2014) appear to be able to tolerate mixing zone and freshwater conditions. Both marine (e.g.…”
Section: Are Tideless Estuaries In Brackish Seas Zones Of Facilitatedmentioning
confidence: 99%